Learning Disorders Across the Lifespan A Mental Health Framework - Margolis, Amy E.; Broitman, Jessica (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book addresses the need to view specific learning disorders (SLDs) within a mental health framework, as supported by their placement alongside autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). It describes how policy and practice point to a different perspective - specifically that SLDs are often treated as educational rather than psychological problems - and examines the implications of this dichotomy. The book reviews empirical research that suggests children need access to treatment for clinical components of SLDs that may respond to psychological intervention separately from, and in addition to, educational interventions. It provides a theoretical framework for organizing research findings and clinical perspectives that support understanding the clinical components of SLDs and addresses the need for a mental health framework within which to approach theory, treatment, and assessment of SLDs. Key areas of coverage include: Examining different theoretical orientations to learning disorders (e.g., cognitive, behavioral, neuropsychoeducational, psychoanalytic). Adapting evidence-based therapeutic techniques for use with children and adolescents who have learning disorders. The need for accurate and well characterized assessment of SLDs. How incorporating a cognitive neuroscience perspective into assessment can move LD treatment and research forward. Learning Disorders Across the Lifespanis an essential reference for clinicians, therapists, and other professionals as well as researchers, professors, and graduate students in school and clinical child psychology, special education, speech-language therapy, developmental psychology, pediatrics, social work as well as all interrelated disciplines.
Part I. Theoretical Framework of the Psychology of Learning Disorders in Children and Adolescents -- Chapter 1. Introduction to the Psychology of Learning Disorders in Children and Adolescents -- Chapter 2. Learning Disorders Are Complex Psychological Problems -- Chapter 3. Social and Economic Factors in LD Policy -- Chapter 4. Self-Psychology as an Underlying Framework for Understanding LD -- Chapter 5. Psychoanalytic Theory and LD -- Chapter 6. Cognitive Efficiency Model of LD -- Chapter 7. Psychology in Schools Designed for Children with LD -- Part II. Treatment of Learning Disorders in Children and Adolescents -- Chapter 8. An Evidence-Based Psychological Treatment for LD: The "I Can Succeed Program" -- Chapter 9. An Evidence-Based Program to Deliver CBT for Anxiety When Teaching Reading -- Chapter 10. Neuropsychoeducational Treatment for LD -- Chapter 11. Using Psychoanalytic Techniques and Theory to Conceptualize and Treat LD -- Chapter 12. Modifying Cognitive Behavioral Therapy for Individuals with NVLD and Concurrent Anxiety or Obsessive Compulsive Disorder -- Chapter 13. Psychiatry and LD -- Chapter 14. Treating OCD in the Presence of LD -- Chapter 15. Using Dialectical Behavior Therapy with Individuals Who Have LD -- Part III. Assessment of the Psychology of Learning Disorders in Children and Adolescents -- Chapter 16. Applying Therapeutic Assessment Approaches to LD: Assessment Is the Beginning of Treatment -- Chapter 17. Preventing Misattribution of Learning Disorder Symptoms to Psychopathology -- Chapter 18. Defining Specific Learning Disorder: The Evolution of the Diagnostic Criteria -- Chapter 19. The Importance of Neuropsychological Assessment for LD -- Chapter 20. Future Directions and Interventions in the Psychology of Learning Disorders in Children and Adolescents.
Keywords: School Psychology; Developmental psychology; Speech therapy; Social psychiatry; Pediatrics; School Psychology; Child and Adolescence Psychology; Speech and Language Therapy; Clinical Social Work; Developmental Psychology; Pediatrics